Penguatan Kapasitas Pemahaman Hak Akses dan Pemantauan Akses Internet Melalui Pelatihan Berbasis Komunitas Desa di Kabupaten Cirebon - Unggul Sagena; Nabillah Saputri Djaelani; Khusnul Amalia (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
The development of infrastructure in Indonesia which targets rural connectivity in 3T areas (Disadvantaged, Outermost, Foremost) means that village communities must prepare themselves. Especially in ensuring the fulfillment of digital rights. There are three digital rights, namely the right to access the Internet (right to access), the right to express online (right to express), and the right to feel safe in the digital realm (right on safety). For this reason, training to increase understanding of Internet access rights as well as training to monitor access based on rural communities is important. Village community-based capacity building training was carried out for representatives of villages, namely Kalikoa, Purbawinangun, Sutawinangun, Astanajapura, Munjul, Buntet and Ciperna villages. This training has the impact of increasing the capacity of the village community in knowledge and understanding of Internet access, and increasing the technical capacity for monitoring and reporting skills through existing tools. The results of the training showed good learning and increased capacity. This is shown by (1) increasing understanding through the pretest and posttest. Internet Knowledge becomes Very Knowledgeable (35.7%) and Knowledgeable (64.3%). Disagree (78.6%) with Internet disruptions and blackouts, and have the right to protest when digital rights violations occur (85.7%). (2) The results of the discussion metaplan show the problem mapping and alternatives developed; and (3) the practice of testing internet networks, both during training and after training, shows that the community can monitor and carry out independent testing.